Defining the pressures of a fluid in a nanoporous, heterogeneous medium - Galteland, Olav; Rauter, Michael T.; Varughese, Kevin K.; Bedeaux, Dick; Kjelstrup, Signe (Frontiers in Physics, 2022)
We describe the thermodynamic state of a single-phase fluid confined to a porous medium with Hill's thermodynamics of small systems, also known as nanothermodynamics. This way of defining small system thermodynamics, with a separate set of control variables, may be useful for the study of transport in non-deformable porous media, where presently no consensus exists on pressure computations. For a confined fluid, we observe that there are two pressures, the integral and the differential pressures. We use molecular simulations to investigate and confirm the nanothermodynamic relations for a representative elementary volume (REV). For a model system of a single-phase fluid in a face-centered cubic lattice of solid spheres of varying porosity, we calculate the fluid density, fluid-solid surface tension, replica energy, integral pressure, entropy, and internal energy.